2022
DOI: 10.1155/2022/4263393
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Effects of Core Stabilization Training on the Cobb Angle and Pulmonary Function in Adolescent Patients with Idiopathic Scoliosis

Abstract: Objective. To observe the effects of core stabilization training on the Cobb angle, respiratory muscle strength (maximum inspiratory pressure, MIP; maximal expiratory pressure, MEP), and pulmonary function (forced vital capacity, FVC; forced expiratory volume, FEV1.0; FEV1.0/FVC%) in adolescent patients with idiopathic scoliosis (AIS) and offer practical-based evidence for the rehabilitation treatment for AIS patients. Methods. 36 AIS patients were assigned to the core stability training (CST) group (n = 18) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Research suggests that the transverse abdominal muscle and internal oblique abdominal muscle can not only enhance the stability of the spine and pelvis but also increase the abdominal pressure [13], which can not only change the scoliosis state but also peel off the adhesion of the ligament soft tissue, improve the muscle blood supply, and enhance its elasticity, and the soft tissue and ligament can also be softened. The results of this study showed that after 12 weeks of core stability training, the Cobb angle of AIS patients in the exercise group decreased significantly, and the results are consistent with that of previous scholars [11]. In addition, this study also found that during the 12 weeks of experiment, the Cobb angle of the AIS group increased from 15:71 ± 2:70 degrees to 16:07 ± 2:95, suggesting that AIS patients were at risk of aggravating spinal deformity without any treatment.…”
Section: Effect Of Core Stability Training On Cobb Angle In Aissupporting
confidence: 92%
See 1 more Smart Citation
“…Research suggests that the transverse abdominal muscle and internal oblique abdominal muscle can not only enhance the stability of the spine and pelvis but also increase the abdominal pressure [13], which can not only change the scoliosis state but also peel off the adhesion of the ligament soft tissue, improve the muscle blood supply, and enhance its elasticity, and the soft tissue and ligament can also be softened. The results of this study showed that after 12 weeks of core stability training, the Cobb angle of AIS patients in the exercise group decreased significantly, and the results are consistent with that of previous scholars [11]. In addition, this study also found that during the 12 weeks of experiment, the Cobb angle of the AIS group increased from 15:71 ± 2:70 degrees to 16:07 ± 2:95, suggesting that AIS patients were at risk of aggravating spinal deformity without any treatment.…”
Section: Effect Of Core Stability Training On Cobb Angle In Aissupporting
confidence: 92%
“…Table 1 shows the basic information of the subjects. [11] is designed on the basis of previous studies; all participants performed the core stability training for 12 weeks (3 sessions per week, 60 min each session). Each session includes 10 minutes of warm-up and 5 minutes of relaxation (both stretching and posture exercises of large muscle groups) and 45 minutes of core stability exercise intervention.…”
Section: Object and Methodsmentioning
confidence: 99%
“…The measurement above observed CA and PS (26.6% and 3.23%) (Figure 7), wherein priorly the core stabilization treatment might improve 15.5% of the Cobb Angle. [10] Otherwise, in this study, the proper ergonomic posture could play role in the improvements, but the movement needs to be done correctly and regularly especially for early AIS patients (10-14 years old) due to the body growth spurt so that their vertebrae can grow normally and stay in the midline. [11] Regarding muscle mechanics, most practice uses muscle tractionto simulate thecurved muscles onspinal loading such asmuscle traction forces between origin andcurved muscle insertion that are typically transmitted to the vertebral bodies or other body parts via "passing points" making contact forces between muscles and vertebral bodies to simulate proper action that wraps around the muscle.…”
Section: Discussionmentioning
confidence: 98%
“…In this study, underweight students with postural scoliosis may have scored low in sit-ups due to insufficient core strength, therefore it is important for schools and teachers to pay special attention to underweight students with poor sit-up test performance, as this may indicate an imbalance in spine or even scoliosis. In regular physical education classes, these affected students should be given additional training to strengthen their core muscles, balance the imbalanced muscle strength on both sides of the spine, and adjust poor posture through the combined action of superficial and deep muscles to correct spinal deformity development (Qi et al, 2022).…”
Section: Postural Scoliosis Has a Profound Impact On The Physical Hea...mentioning
confidence: 99%